2021
DOI: 10.1002/jum.15774
|View full text |Cite
|
Sign up to set email alerts
|

Z‐Score Reference Ranges for Umbilical Vein Diameter and Blood Flow Volume in Normal Fetuses

Abstract: Objectives To establish Z‐scores for the diameter and blood flow volume of the umbilical vein (UV) in normal fetuses. Methods This was a prospective study involving 907 normal fetuses. We measured the diameter (Duv) of two different segments of the UV (FUV: the free loop of the UV; FIUV: the fetal intra‐abdominal UV). Next, we calculated the blood flow volume (Quv). Z‐scores were created for both Duv and Quv using gestational age, femur length, and biparietal diameter as independent variables. Results We succe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 31 publications
1
10
0
Order By: Relevance
“…Our results showed that Duv, Vmax and Quv increased with GA, while UAPI decreased as pregnancy proceeded under normal circumstances. The alterations in Duv, Vmax, Quv and UAPI were consistent with previous studies on umbilical vein blood flow (1,11,13). Although the placental blood flow also increased with fetal body weight, the nQuv declined slightly with gestational age.…”
Section: Discussionsupporting
confidence: 90%
“…Our results showed that Duv, Vmax and Quv increased with GA, while UAPI decreased as pregnancy proceeded under normal circumstances. The alterations in Duv, Vmax, Quv and UAPI were consistent with previous studies on umbilical vein blood flow (1,11,13). Although the placental blood flow also increased with fetal body weight, the nQuv declined slightly with gestational age.…”
Section: Discussionsupporting
confidence: 90%
“…A progressive and exponential increase in placental blood flow in the human fetus can be observed throughout gestation. Several studies [4][5][6][7][8][9][12][13][14]16,[27][28][29] obtained an estimate of the umbilical vein blood flow. 21,30 The absolute blood flow volume in umbilical vein increases around 7-fold in the second half of the pregnancy 6 (i.e., from 63 ml/ min at 20 weeks to 373 ml/min at 38 weeks 8 ) (Figure 5; data unpublished, presented at ISUOG World Congress 2022).…”
Section: Umbilical Vein Blood Flow In Normal Pregnancymentioning
confidence: 99%
“…As an example, Figure 3 illustrates where I believe the reference interval lines should be placed in Figure 2F of the Wang study. 1 In summary, I would suggest the authors (1) correct the standard deviation equation for the umbilical vein diameter measured in the amniotic fluid, (2) explain how they know they were in the center of the umbilical vein for their measurements of the vein diameter, and (3) re-analyze their data and select the equations using fractional polynomial regression to compute the mean and standard deviation that represents the reference intervals. [2][3][4] Unless this is done, Z-score computations will not be accurate.…”
mentioning
confidence: 99%
“…Figure 1F and H of the Wang study shows a "pulsatile" waveform of the umbilical vein. 1 This is highly unusual as the venous flow is "flat," except when the fetus is breathing. Why were these images selected as an example when umbilical venous flow is usually nonpulsatile?…”
mentioning
confidence: 99%
See 1 more Smart Citation